Problematic issues at sepsis diagnosis (Review and discussion) - S. D. Shapoval; D. А. Smirnova; V. O. Belinska (Сучасні медичні технології)
Topical issues of modern diagnostics of sepsis, potential problems of assessing the patient's condition and ways of solving problematic issues of timely diagnosis and prevention of sepsis development are analysed.